Modelling root decomposition effects on root reinforcement and slope stability - Phan, Trung Nghia; Leung, Anthony Kwan; Nguyen, Thanh Son; Kamchoom, Viroon; Likitlersuang, Suched (My University, 2025)
This study investigates the influences of root decomposition of two vetiver species on mechanical root shear reinforcement and vegetated slope stability. The transient variations of maximum root shear reinforcement (Cr,max) of vetiver species was examined by combining the extended Root Bundle Model with the modified Wu's model. Existing laboratory data of the biomechanical properties (i.e., tensile strength, secant modulus) and morphological traits (i.e., diameter distribution, root length, orientation) of the decomposing roots following herbicide application were used as input parameters in the root reinforcement models to predict the root shear reinforcement. The predicted Cr,max was then used in the slope stability analysis on the basis of Morgenstern-Price method to evaluate the temporal variation in the stability of vegetated slope with different slope angles and plant killing patterns. The combined model was capable of predicting the exponential reductions in Cr,max following the transient declines in the root strength, secant modulus and diameter. The large variability in the tensile strength of decomposing roots could also be well captured through the use of Weibull survival function. The slope stability analysis highlighted that the vetiver roots contributed the most to the stability of slope when the slope angle was less than 45°. Additionally, it is recommended to refrain from killing the plants grown near the slope's toe, because this region is particularly susceptible to shallow slope failure.
Keywords: Root decomposition; Root reinforcement model; Shear strength; Slope stability; Soil bioengineering